Rheumatology at the general practitioner/hospital interface: a study of prevalence and access to specialist care. Issue 12 (December 1990) - Sullivan, F M; Barber, J H; Sturrock, R D
Abstract : Four general practices with a combined population of 23, 300 in the west of Scotland participated in a record research and questionnaire assessment of 551 patients with rheumatic diseases. The study describes the prevalence, levels of disability found, and the types of service used. Even with this number of patients it was not possible to detect any significant differences in disability levels, use of second line drugs, or aids/appliances when comparing practices with adequate or inadequate access to rheumatological facilities (general practitioner perception). General practice is an appropriate setting in which to investigate the effect of service provision, but larger studies will be needed to reach more definite conclusions.